Foraging Behavior of Northern Bobwhites in Relation to Resource Availability - Ryan S. Miller; William E. Palmer; Shane D. Wellendorf; L. Wes Burger Jr. (National Quail Symposium Proceedings, 2017)
Distribution of food resources may influence northern bobwhite (Colinus virginianus) foraging decisions and demographic rates. We tested whether covey movements were sensitive to food availability by spreading sorghum (Sorghum bicolor) every 15 days at 3 rates; high rate (174 L/ha/yr), low rate (44 L/ha/yr), and no feed on 3 sections ( 240 ha each) of Tall Timbers Research Station, 2009–2010. We measured sorghum availability spread along a 17 km feeding trail every 5 days. We determined seasonal (1 Nov - 15 Mar) home ranges of radio-tagged coveys (n = 89) and daily movement rates and home ranges of a subset of coveys located every 30 mins, sunrise to sunset (1 Feb - 15 Mar). Diet was determined from harvested bobwhites. Mean sorghum availability (seeds/0.5m2) on the feed trail declined from 50 seeds at day 1 to 12 seeds at day 15, and 11 seeds at day 1 to 0 seeds at day 10, for high and low rates, respectively. Seasonal home ranges did not differ among treatments; however, daily home ranges were smaller for coveys on the high rate areas, as was dispersion of locations within home ranges. Distances to the feed trail from covey and random locations were similar. There was no difference in distance traveled (25.20 m; SE = 0.65) between consecutive covey locations among treatments. Proportion of sorghum in the diet declined precipitously when <15 seeds/0.5m2. We estimated an empirical giving up density of 10–14 seeds/0.5m2, 1.6 kcals/0.5m2. Food availability, even at high levels, marginally affected covey space use and movement rates during late winter. Other factors affecting bobwhites, such as predator avoidance, or thermal regulation, may have a more significant effect on bobwhite covey daily movements and space use.
Keywords: colinus virginianus; northern bobwhite; behavior; foraging movements; range; supplemental feed; telemetry